Mineral composition of mafic minerals and ore deposition from the Kassiteres (Sappes) and Pagoni Rachi ( Kirki) porphyry Cu-Mo prospects / W. Thrace - ΒΟΥΔΟΥΡΗΣ, Π. (Bulletin of the Geological Society of Greece, 2001)
The porphyry Cu-Mo mineralizations at Kassiteres and Pagoni Rachi are genetically related with dioritic to dacitoandesitic subvolcanic rocks that were and preliminary microthermometric data indicate that the hypogene mineralizations were introduced during albitic / potassic alteration of the intrusives and temperatures about 400°C from boiling magmatic-hydrothermal fluids. Electron microprobe major element analyses are presented for magmatic and hydrothermal biotites and amphiboles from both occurences. Hydrothermal biotites in the albitic / potassic zones are more magnesian than their magmatic counterparts and therefore close to phlohopite end - member composition. The amphiboles from Kassiteres range from magnesio - hornblende to actinolite, commonly within the same grain. Moreover the chemical data in both magmatic and hydrothermal biotites and amphiboles from the above two occurences indicate a Mg - and Si - enrichment and a Ti - depletion during crustallization and cooling from magmatic to late magmatic - early hydrothermal conditions. It is likely that an increase in oxyzen fugacity accompanied their chemical evolution. This oxidation trend is associated with the fluid exsolution of the magmas resulting in the development of the studied porphyry type mineralizations. Elements, which are also depleted from Mg - rich (more oxidized) amphiboles and biotites (K, Na, Fe and Ti) are partitioned in the magmatic - hydrothermal fluid phase and are responsible for the albitic / potassic altaration of both occurences.